Evaluation of polymyxin B AUC/MIC ratio for dose optimization in patients with carbapenem-resistant Klebsiella pneumoniae infection - Wang, Peile; Liu, Shaohua; Qi, Guangzhao; Xu, Min; Sun, Tongwen; Yang, Jing (Frontiers in Microbiology, 2023)
Polymyxin B has been used as a last-line therapy for the treatment of carbapenemresistant gram-negative bacteria infection. Pharmacokinetics/pharmacodynamics index (AUC/MIC) of polymyxin B has not been clinically evaluated, given that the broth microdilution method for polymyxin susceptibility testing is rarely used in hospitals.This study included 77 patients with Carbapenem-resistant Klebsiella pneumoniae infections. Among them, 63 K. pneumoniae isolates had MIC values of 1.0 mg/L by broth microdilution but 0.5 mg/L in Vitek 2 system. Polymyxin B AUC/MIC was significantly associated with clinical response (P = 0.002) but not with 30-day all-cause mortality (P = 0.054). With a target AUC/MIC value of 50, Monte Carlo simulations showed that a fixed dose of 100 mg/12h and three weight-based regimens (1.25 mg/kg/12h for 80 kg and 1.5 mg/kg/12h for 70 kg/80 kg) achieved cumulative fraction of responses > 90% regardless of renal function, but the risk of nephrotoxicity was high.